Quadruple Helix Model in Building Communalism and Social Resilience in Handling Poverty in Rural Communities - Chandra Dinata (University of Merdeka Malang, 2023)
Poverty is a major problem in a country's development policy. Various strategies were implemented in an effort to reduce poverty, including utilizing economic resources ement of social resources as a new form of actor involvement in the quadruple helix model in handling local poverty problems. This method is a qualitative research paradigm is an approach used in the process of collecting data related to the involvement of social resources in social security to reduce local poverty rates. Data were analyzed interactively and triangulation was used to obtain validity. This article is the result of research on poverty management in rural communities. The high poverty gap between urban and rural communities encourages this research to be carried out. The multidimensional causes of poverty encourage a paradigm shift in handling, namely by involving multi actors through the quadruple helix model to build communalism and social resilience. The results of this study indicate that the social spirit generated from social institutions can be used as the glue for communalism in poverty reduction, so that it becomes a helix in government efforts to reduce poverty. Social togetherness as a form of solidarity from community groups present in the behavior and actions of groups is a social resource that is capable of creating community social resilience so that it can move togetherness in handling local poverty problems. to stimulate the income of poor groups of people. A structural approach is taken by the government in carrying out a poverty alleviation strategy. This study describes the involvement of social resources as a new form of actor involvement in the quadruple helix model in handling local poverty problems. This method is a qualitative research paradigm is an approach used in the process of collecting data related to the involvement of social resources in social security to reduce local poverty rates. Data were analyzed interactively and triangulation was used to obtain validity. This article is the result of research on poverty management in rural communities. The high poverty gap between urban and rural communities encourages this research to be carried out. The multidimensional causes of poverty encourage a paradigm shift in handling, namely by involving multi actors through the quadruple helix model to build communalism and social resilience. The results of this study indicate that the social spirit generated from social institutions can be used as the glue for communalism in poverty reduction, so that it becomes a helix in government efforts to reduce poverty. Social togetherness as a form of solidarity from community groups present in the behavior and actions of groups is a social resource that is capable of creating community social resilience so that it can move togetherness in handling local poverty problems.